The least you should know about English writing skills : form C - Wilson, Paige; Glazier, Teresa Ferster (Wadsworth Cengage Learning, 2014)
With Wilson and Glazier's THE LEAST YOU SHOULD KNOW ABOUT ENGLISH: WRITING SKILLS, you'll improve your word choice, punctuation, and sentence structure as you develop as a writer. Extensive sets of exercises complement the textbook's brief, clear explanations. These timely, often humorous exercises will engage you in the mechanics of writing by allowing you to practice what you've learned and receive immediate feedback from answers provided at the back of the book